PERAN PRODUCT CUES AND RISK AVERSION PADA PURCHASE INTENTION DAN POST PURCHASE FEELINGS - Sri Rejeki Ekasasi; Ayu Hema Ajeng Diwasasri (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2013)
AbstractThe research aimed to investigate the influence of extrinsic cues and intrinsic cues and risk aversion towards purchase intention and post-purchase feeling of counterfeited computer software and music CD. This research study collected data from two populations which are students and employee. Approximately 128 respondents involved to give respond for the survey. The analysis using Structural Equation Model (SEM) show that product cues and risk aversion give different significant impact towards purchase intention and post-purchase feeling of counterfeited computer software and music CD. The research concluded that risk aversion and extrinsic cues has a significant influence to purchase intention of counterfeited computer software while it does not appear similar result to music CD. Moreover, the study revealed that for both counterfeited computer software and music CD, the purchase intention is proven to have negative significant influence towards post-purchase feelings.Keywords: risk aversion, extrinsic cues, intrinsic cues, purchase intention, post-purchase feelingsAbstrakTujuan dari penelitian ini adalah untuk melihat pengaruh atribut ekstrinsik dan intrinsic produk serta aspek menolak resiko terhadap niat beli dan perasaan paska beli software computer dan CD music bajakan. Penelitian ini diharapkan akan memperoleh sebuah model dengan pendekatan cultural dan strategi bisnis untuk memblokir atau mengurangi produk bajakan yang dapat diakses konsumen di pasar. Data primer akan dikumpulkan dari dua populasi, kelompok mahasiswa dan kelompok pekerja, dari empat kota besar di Indonesia yaitu Jakarta, Semarang, Surabaya, dan Yogyakarta. Lebih kurang 128 responden terlibat dalam penelitian ini. Hasil penelitian menunjukkan bahwa aspek atribut produk yang bersifat ekstrinsik dan aspek menolak resiko terbukti memiliki hubungan signifikan mempengaruhi niat beli software computer, akan tetapi lain tidak demikian pada niat beli CD music bajakan. Lebih lanjut, hasil penelitian menunjukkan bahwa niat beli produk bajakan memiliki hubungan negatif yang signifikan terhadap perasaan paska beli software computer dan CD music bajakan.Keywords: aspek menolak resiko, atribut ekstrinsik produk, atribut intrinsik produk, niat beli, perasaan paska beli